2012
DOI: 10.1128/jvi.00808-12
|View full text |Cite
|
Sign up to set email alerts
|

Defective Antiviral Responses of Induced Pluripotent Stem Cells to Baculoviral Vector Transduction

Abstract: Genetic engineering of induced pluripotent stem cells (iPSCs) is important for their clinical applications, and baculovirus (BV)holds promise as a gene delivery vector. To explore the feasibility of using BV for iPSCs transduction, in this study we first examined how iPSCs responded to BV. We determined that BV transduced iPSCs efficiently, without inducing appreciable negative effects on cell proliferation, apoptosis, pluripotency, and differentiation. BV transduction slightly perturbed the transcription of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Therefore, the IFN system, which is the central part of innate immunity in differentiated somatic cells [14], is not fully functional in ESCs. Together with the similar findings in induced pluripotent stem cells [15] and embryonal carcinoma [16], an underdeveloped antiviral innate immunity represents an intrinsic property of all pluripotent cells (reviewed in Guo et al [17]). …”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the IFN system, which is the central part of innate immunity in differentiated somatic cells [14], is not fully functional in ESCs. Together with the similar findings in induced pluripotent stem cells [15] and embryonal carcinoma [16], an underdeveloped antiviral innate immunity represents an intrinsic property of all pluripotent cells (reviewed in Guo et al [17]). …”
Section: Introductionmentioning
confidence: 97%
“…Indeed, it has been demonstrated that ESCs do not show immune responses typically seen in differentiated cells when infected with bacteria and viruses (14,15). Our recent studies in mouse ESCs (mESCs) (1618) and those from other investigators in human ESCs (hESCs) and in induced pluripotent stem cells (iPSCs) (19,20) demonstrated that the IFN system, the central component of innate antiviral immunity in differentiated somatic cells (21), is not fully developed in these cells. Therefore, the lack of innate immune responses to both bacterial and viral infection appears to be an intrinsic property of all pluripotent stem cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Nayak et al 19 reported that graphene-treated human mesenchymal stem cells show enhanced proliferation and differentiation. Chen et al 20 reported that graphene and GO can support induced pluripotent stem cell culture and allow for spontaneous differentiation, and also suggested that the different surface properties of graphene and GO influence the performance of induced pluripotent stem cell culture and applications. The different physical and chemical properties could influence the biological responses of cells.…”
Section: Introductionmentioning
confidence: 99%